FAKTOR-FAKTOR YANG BERHUBUNGAN DENGAN MINAT MASYARAKAT DALAM KEIKUTSERTAAN BPJS MANDIRI DI KECAMATAN BENER KABUPATEN PURWOREJO - Melinda Melinda; Anneke Suparwati; Antono Suryoputro (Fakultas Kesehatan Masyarakat Universitas Diponegoro, 2016)
Bener District located in Purworejo. The problem that exists is the number of participants health BPJS is small in scope, with details of the number of participants health BPJS consisted of 8.153 households PBI participants and 695 households NON PBI participants. Other data showed 8.151 household qualify as poor family and 10.581 household qualify as Non Gakin, there’s 6,5% Non PBI health BPJS participants of the total Non Gakin population. We need to know why 93,5% well off households in Bener District has not followed BPJS. The purpose of this study was to determine the factors associated with the public interest in participation of health BPJS independently in Bener Regency. This is an analytical explanatory research. The method used was survey through questionnaire and interviews with a cross-sectional design. Samples were well off family who have not joined health BPJS living in Bener District. The sampling using probability sampling with proportional random sampling. Determination of sample size use of Lemeshow is 65 households. Respondents mostly middle age category (41-60 years) as many as 55 households (67.9%). Respondents had an average age of 47.51 years old, the majority of respondents finished primary school as many as 37 households (45.7%), livelihood as a self-employed as many as 32 households (39.5%), and are not interested in participation of health BPJS as many as 67 households (82.7%) althought the variables were showed good result. It’s may caused by the influenced of other variables which is out of investigated variables. The results of the study showed that the factors relating to the public interest in the participation of independent health BPJS is attitudes, perceptions, and the support of those closest to the respondent. But the knowledges, economic situations, and behavior control are not related.